Analysis of Activeness and Critical Thinking of Students in MA Al-Djufri Blumbungan - Zamroni, Toib; Ulfa, Maria; Ulfa, Winda Maria; Sa'adah, Kamilatus; Jannah, Aesyatul; Oktaviani, Trifitriyanti; Ibana, Lukluk (Lombok Institute, 2024)
This study aims to analyze the activeness and critical thinking skills of students in Class XII MA Al-Djufri Blumbungan. A quantitative research approach was employed, utilizing questionnaires as the primary data collection method. The study focused on biology, with a sample of 20 students. Data on student engagement were collected through classroom observations, focusing on participation in discussions, responses to teacher questions, and peer interactions. The findings indicate that student engagement is generally classified as medium to high. However, the critical thinking skills of students are categorized as low, with less than 60% of students demonstrating critical thinking abilities. The results highlight the need for enhanced pedagogical strategies to foster both engagement and critical thinking in the classroom.